A performance-based damage-control design procedure of hybrid steel MRFs with EDBs. (April 2018) - Ke, Ke; Yam, Michael C.H.
Abstract: A noteworthy feature of the hybrid steel moment resisting frames (MRFs) with energy dissipation bays (EDBs) is the damage-control behaviour characterised by concentration of plastic damages in the energy dissipation bay (EDB) under earthquakes. This paper presents a design methodology for conducting the damage-control design of hybrid steel MRFs with EDBs. First, the structural damage-control behaviour quantified by the classical bilinear kinematic hysteretic model with significant post-yielding stiffness ratio is clarified utilising the test results extracted from a large-scale quasi-static test programme. Then, based on the seismic energy balance of single-degree-of-freedom systems incorporating significant post-yielding stiffness ratios, the design philosophy and governing energy balance equations featuring the damage-control behaviour of low-to-medium rise hybrid steel MRFs with EDBs under earthquake ground motions are presented. Subsequently, a stepwise design procedure that can be used to search for a design strategy of a hybrid steel MRF with EDBs under expected ground motions is developed. Three low-to-medium rise prototype structures are designed by the proposed methodology, and the seismic responses of the systems are evaluated by pushover analyses and nonlinear response history analyses based on numerical models validated by the test results. The results indicate that all the prototype hybrid steel MRFs with EDBs can achieve the damage-control behaviour with the prescribed drift threshold, and hence the post-earthquake residual deformations are also mitigated. Since the proposed method is a direct-iterative design procedure, it also retains practical attractiveness and will facilitate the seismic design of hybrid steel MRFs with EDBs. Highlights: The single-degree-of-freedom system analogy is utilised. The damage-control behaviour is quantified by energy balance concept. A direct-iterative damage-control design procedure is developed. The procedure is validated by seismic response analyses of prototype systems.